Demokrasi Islam Indonesia: Kajian Kontrasif antara Nurcholish Majid dan Al-Maududi - Anisa, Anisa; Hamzah, Nur; Rosdiawan, Ridwan; Tisna, Tisna (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study contrastively analyzes the thoughts of Nurcholish Madjid and Abul A'la Al-Maududi on the concept of democracy in Islam. Using a descriptive qualitative method and a literature review approach, this study explores the fundamental differences in the two figures' views on the relationship between Islam and democracy. Nurcholish Madjid emphasizes the compatibility of Islam with modern democracy through the concepts of secularization (desacralization) and pluralism, by placing religion as a source of moral values without having to become a formal political institution. In contrast, Al-Maududi proposed the concept of theodemocracy that emphasizes the supremacy of sharia and the sovereignty of God (hakimiyyatullah) in the government system. The results showed that the differences in the thinking of the two figures were influenced by different socio-political contexts: Madjid was influenced by the reality of Indonesian pluralism and Islamic modernism, while Al-Maududi was influenced by the experience of colonialism and efforts to maintain Islamic identity in India. Despite their different approaches, both emphasized the importance of deliberation and the role of Islam as moral guidance in the state. This study contributes to a more comprehensive understanding of the varied interpretations of the relationship between Islam and democracy in the modern context.